Rapid quantitative analysis of individual anthocyanin content based on high‐performance liquid chromatography with diode array detection with the pH differential method. Issue 18 (28th July 2014) - Wang, Huayin
<x xml:space="preserve">Abstract</x> A new quantitative technique for the simultaneous quantification of the individual anthocyanins based on the pH differential method and high‐performance liquid chromatography with diode array detection is proposed in this paper. The six individual anthocyanins (cyanidin 3‐glucoside, cyanidin 3‐rutinoside, petunidin 3‐glucoside, petunidin 3‐rutinoside, and malvidin 3‐rutinoside) from mulberry (Morus rubra) and Liriope platyphylla were used for demonstration and validation. The elution of anthocyanins was performed using a C18 column with stepwise gradient elution and individual anthocyanins were identified by high‐performance liquid chromatography with tandem mass spectrometry. Based on the pH differential method, the high‐performance liquid chromatography peak areas of maximum and reference absorption wavelengths of anthocyanin extracts were conducted to quantify individual anthocyanins. The calibration curves for these anthocyanins were linear within the range of 10–5500 mg/L. The correlation coefficients (r2) all exceeded 0.9972, and the limits of detection were in the range of 1–4 mg/L at a signal‐to‐noise ratio ≥5 for these anthocyanins. The proposed quantitative analysis was reproducible with good accuracy of all individual anthocyanins ranging from 96.3 to 104.2% and relative recoveries were in the range 98.4–103.2%. The proposed technique is performed without anthocyanin standards and is a simple, rapid, accurate, and economical method to determine individual anthocyanin contents.